Investigating representations of facial identity in human ventral visual cortex with transcranial magnetic stimulation - Gilaie-Dotan, Sharon; Silvanto, Juha; Schwarzkopf, Dietrich S.; Rees, Geraint (Frontiers in Human Neuroscience, 2010)
The occipital face area (OFA) is face-selective. This enhanced activation to faces could reflect either generic face and shape-related processing or high-level conceptual processing of identity. Here we examined these two possibilities using a state-dependent transcranial magnetic stimulation (TMS) paradigm. The lateral occipital (LO) cortex which is activated non-selectively by various types of objects served as a control site. We localized OFA and LO on a per-participant basis using functional MRI. We then examined whether TMS applied to either of these regions affected the ability of participants to decide whether two successively presented and physically different face images were of the same famous person or different famous people. TMS was applied during the delay between first and second face presentations to investigate whether neuronal populations in these regions played a causal role in mediating the behavioral effects of identity repetition. Behaviorally we found a robust identity repetition effect, with shorter reaction times when identity was repeated, regardless of the fact that the pictures were physically different. Surprisingly, TMS applied over LO (but not OFA) modulated overall reaction times, compared to the No TMS condition. But critically, we found no effects of TMS to either area that were modulated by identity repetition. Thus, we found no evidence to suggest that OFA or LO contain neuronal representations selective for the identity of famous faces which play a causal role in identity processing. Instead, these brain regions may be involved in the processing of more generic features of their preferred stimulus categories.